Roles of Akt and ERK in mTOR-Dependent Antidepressant Effects of Vanillic Acid - Chuang, Han-Wen (ACS Omega, 2020)
[Image: see text] Vanillic acid, an oxidized form of vanilla, is a flavoring agent with a creamy odor. Several studies have reported the neuroprotective effects of vanillic acid, which are predominantly associated with anti-inflammatory and antioxidative properties. The anti-inflammatory and antioxidative properties may result from Akt or ERK signaling activation. The activation of the mammalian target of rapamycin (mTOR), a key downstream target of Akt and ERK signaling, is a crucial therapeutic target for treating depression. However, the antidepressant effects of vanillic acid remain unknown. The present study applied the forced swim test (FST) to investigate the antidepressant effects of vanillic acid and its association with Akt, ERK, and mTOR signaling and upstream α-amino-3-hydroxy-5-methyl-4-isoxazolepropionaic acid receptor (AMPAR) in the prefrontal cortex (PFC) of mice. Vanillic acid demonstrated antidepressant effects by significantly reducing behavioral despair in the FST. None of the treatments changed locomotor activity. Additionally, vanillic acid increased AMPAR throughput, Akt, and mTOR signaling but not ERK signaling in the PFC. NBQX (an AMPAR blocker), MK 2206 (an Akt blocker), and rapamycin (an mTOR blocker) used in pretreatment attenuated the antidepressant effects of vanillic acid, but SL327 (an ERK inhibitor) did not. The immunochemical results indicated that the antidepressant effects of vanillic acid depend on the AMPAR–Akt–mTOR signaling transduction pathway. Our findings reveal an Akt-dependent, but ERK-independent, the mechanism underlying the antidepressant effects of vanillic acid, which may be beneficial for some patients with depression.